Influence of Calcium Sulfate Type on Evolution of Reaction Products and Strength in NaOH- and CaO-Activated Ground Granulated Blast-Furnace Slag - Seyoon Yoon (Applied Sciences, 2018)
This study investigated the influences of CaSO4 type (i.e., anhydrite vs. gypsum) on strength development and reaction products in the activation of ground granulated blast-furnace slag (GGBFS) when different activators (i.e., CaO vs. NaOH) and sources of GGBFS were used. In the CaO-activation, the addition of calcium sulfates greatly enhanced 28-day strengths, regardless of the choice of CaSO4 or GGBFS source, through increasing the quantities of reaction products and reducing pore volume and size. However, in the NaOH-activation, the use of calcium sulfates showed the complex dependency of strength on the choice of CaSO4 type and GGBFS source, and it barely produced beneficial effects on the quantity of reaction products and reduction of pore volume and size. Thus, the results in this study indicate that the combination of CaO-activation and calcium sulfates is a more effective means of activating GGBFS to gain enhanced strength and significant quality control than the use of gypsum with NaOH-activation.